Photopyroelectric Technique in Thermal Diffusivity Determination and Spectroscopic Response of Solid Samples - Liaw, Hock Sang (2003)
Conventional photopyroelectric (PPE) measurement of thermal diffusivity of optically opaque sample was done in case of thermally thick sample, but it underwent a great attenuation of signal. In this study, the generalisation of Mandel is and Zver special cases of thermally thin-thick sample has been derived and was used to determine the thermal diffusivity. The method was experimentally tested for aluminium samples of different thickness and copper sample, and the values obtained were close to the literature values. The Bennett and Patty theory in the generation of photoacoustic signal has been successfully adopted in the generation of PPE signal. An equation of complex PPE signal was derived. A normalisation procedure was used to eliminate a number of unknown parameters in PPE cell. The method was experimentally tested for aluminium, copper, and nickel samples, and the values obtained were close to the literature values.